Thrombin and the Coag-Inflammatory Nexus in Neurotrauma, ALS, and Other Neurodegenerative Disorders - Festoff, Barry W.; Citron, Bruce A. (Frontiers in Neurology, 2019)
This review details our current understanding of thrombin signaling in neurodegeneration, with a focus on amyotrophic lateral sclerosis (ALS, Lou Gehrig’s disease) as well as future directions to be pursued. The key factors are multifunctional and involved in regulatory pathways, namely innate immune and the coagulation cascade activation, that are essential for normal nervous system function and health. These two major host defense systems have a long history in evolution and include elements and regulators of the coagulation pathway that have significant impacts on both the peripheral and central nervous system in health and disease. The clotting cascade responds to a variety of insults to the CNS including injury and infection. The blood brain barrier is affected by these responses and its compromise also contributes to these detrimental effects. Important molecules in signaling that contribute to or protect against neurodegeneration include thrombin, thrombomodulin (TM), protease activated receptor 1 (PAR1), damage associated molecular patterns (DAMPs), such as high mobility group box protein 1 (HMGB1) and those released from mitochondria (mtDAMPs). Each of these molecules are entangled in choices dependent upon specific signaling pathways in play. For example, the particular cleavage of PAR1 by thrombin versus activated protein C (APC) will have downstream effects through coupled factors to result in toxicity or neuroprotection. Furthermore, numerous interactions influence these choices such as the interplay between HMGB1, thrombin and TM. Our hope is that improved understanding of the ways that components of the coagulation cascade affect innate immune inflammatory responses and influence the course of neurodegeneration, especially after injury, will lead to effective therapeutic approaches for ALS, traumatic brain injury, and other neurodegenerative disorders.